APPLICATION OF PLAYING METHOD MOBIS TO GROW-BUILD A FINE MOTORIC SKILL AND CREATIVITY OF PRESCHOOL AGE (5-6 years) THROUGH MOBILE ACTIVITIES IN ISLAMIC KINDERGARTEN AN-NISA BANDUNG - efie muf tiati (IKIP Siliwangi Bandung, 2018)
AbstractImplementation of play methods in early childhood has always been a major effort in foster-growinga fine motor skills and creativity. In An-Nisa Bandung kindergarten, the method of playing through Mobis (Motor skills block interlocking system) activities is applied to 20 B-age group students aged 5-6 years to know the success rate of developing motor skills and creativity after 8 times of monitoring in the class. The results of the experimental experiments show a smooth growth rate of fine motor skills average of 70% or included in the category